The Effect of Topical Administration of Asi on Care and Duration of Immunal Cord Removal - Harahap, Novy Ramini; Nurrahmaton, Nurrahmaton; Syari, Mila; Hasanah, Fitri Husratul (Universitas Islam Jember, 2024)
Umbilical Cord Care can also be interpreted as the care of the umbilical cord in a clean state, with efforts to minimize exposure to dust and dirt to prevent infection. Proper and correct umbilical cord care has a positive impact, especially on infants. If we care for the umbilical cord properly, it will also facilitate a quick cord detachment. The objective of this research is to determine the frequency of umbilical cord care and the duration of cord detachment before and after the administration of topical breast milk, the average duration of care, and the influence of topical breast milk administration at Klinik Pratama Shanty in 2023. The research design employed is a